2012
DOI: 10.5539/ass.v8n5p116
|View full text |Cite
|
Sign up to set email alerts
|

Malaysian Newspaper Discourse and Citizen Participation

Abstract: Newspapers are a particularly important tool for the communication of government agenda, policies and issues to the general public. An informed public makes for better democracy and active citizen participation, with citizens able to make well-informed decisions about the governance of their nation. This paper observes the role of Malaysian mainstream newspapers in the facilitation of citizen participation to exercise their political rights and responsibilities through a critical discourse analysis on newspape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…Teo, 2000;Gale, 2004;Gabrielatos & Baker, 2008;Baker et al, 2008;Khosravinik, 2009;McKay et al, 2011). This paper also confirms research done in Malaysia by Pang (2006), Azlan et al (2012) and Gill et al (2012), that there is a strong agenda from government linked media to frame reports in a particular, pro-government way. Had The NST and The Star reported more different voices and used less strategies of mitigation, it would have adopted the "audi alteram partem" approach, which is in line with the ethics of proper journalism.…”
Section: Policy and National Securitysupporting
confidence: 77%
See 1 more Smart Citation
“…Teo, 2000;Gale, 2004;Gabrielatos & Baker, 2008;Baker et al, 2008;Khosravinik, 2009;McKay et al, 2011). This paper also confirms research done in Malaysia by Pang (2006), Azlan et al (2012) and Gill et al (2012), that there is a strong agenda from government linked media to frame reports in a particular, pro-government way. Had The NST and The Star reported more different voices and used less strategies of mitigation, it would have adopted the "audi alteram partem" approach, which is in line with the ethics of proper journalism.…”
Section: Policy and National Securitysupporting
confidence: 77%
“…All newspapers under investigation show a high degree of quoting a single person extensively. This comes as no surprise, since Azlan et al (2012) already provided the insight that government linked media prominently cover Malaysian government officials in a positive way. Most probably Malaysiakini, by quoting Australian government officials, is trying to be non-partisan and to employ a strategy to avoid critical sentences towards Malaysian government officials and to avoid practicing a "progovernment policy" (Pang, 2006, p. 72).…”
Section: Resultsmentioning
confidence: 99%
“…In other words, if youths are important beneficiaries of sustainable development and thus, need to participate in shaping their future, they need to actively participate in discourses that largely shape that future. To join in discussing their future in the media, they need access to media, media literacy, writing, speaking and production skills as well as sufficient interest in discourse topics (Rahim et al, 2012).…”
Section: Statement Of Problemmentioning
confidence: 99%
“…Newspaper is a major medium for political mobilization and political debate (Azlam et al, 2012). It makes information available to enable citizens make informed decisions about politics, economy, security and community life.…”
Section: Expanding Media Arenamentioning
confidence: 99%
“…Little is known about stance in news reports in the Malaysian context. Media framing studies have shown that mainstream newspapers tend to quote government sources whereas alternative newspapers quote opposition leaders and religious leaders as news sources in controversial events, such as the 1Malaysia Development Berhad (1MDB) financial-cum-political scandal involving high-ranking politicians (Murudi & Ting, 2019) and race-related issues (Azlan, Rahim, & Basri, 2012;Ismail & Ahmad, 2014;Khalid, 2011;Yang & De Rycker, 2017;Yang & Ishak, 2012;Yang & Leong, 2017). However, as the researchers are from the field of communication, they do not analyse how the news sources are quoted.…”
Section: Introductionmentioning
confidence: 99%